FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHA TANAMAN HIAS DI KOTA DENPASAR - Wulandari, Nanda Yunita; Wenagama, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Ornamental plant business is one form of MSMEs that provides products in the agricultural sector. The ornamental plant business has become one of the drivers of Indonesia's economic growth and the trend of ornamental plants has been felt since the beginning of the Covid-19 pandemic. This trend shows an increase in the demand for ornamental plants, which is the basis for increasing business income. However, considering the Covid-19 pandemic that has not yet fully ended, it encourages MSME actors, including ornamental plant business players, to digitize in order to maintain business continuity. The purpose of this study was to analyze the factors that influence the income of ornamental plants in Denpasar City. The data used in this study came from raw data using the Slovin formula and were obtained from a sample of 65 respondents. The data collection method used a questionnaire which was then tested and analyzed with the Eviews 10 program. The results of this study indicate that capital, length of business and e-commerce simultaneously have a significant effect on ornamental plant business income in Denpasar City. Partially, capital, length of business and e-commerce have a significant effect on business income of Denpasar City ornamental plants.